The structure of social and humanitarian training of future law enforcement officers (Pedagogy of Higher and Secondary Education, 2021)
Exxence of social-humanitarian preparation of future workers of law enforcement authorities is examined in statt'e. In the article scientific literature is analysed on this question. The author of the article defined a strucrute, maintenance, purpose and tasks of social-humanitarian preparation of future workers of law enforcement authorities.
Keywords: socially is humanitarian preparation; socially personality jurisdictions; professional qualification; humanizing of education